Towards Greener Skies: Natural Fibres for Aeronautical Applications - Balo, Figen; Sua, Lutfu S. (Mouloud Mammeri Univ Tizi-Ouzou, 2025)
Choosing materials mostly involves taking their sustainability into account. The material selection for airplane internal product design is heavily influenced by the enormous demand, knowledge of the ecological effect, and appropriateness among a material's performance, properties, and adequacy for the part to be utilized. In this study, natural fibres for aeronautical applications were chosen using a step-by-step methodology. To have a better understanding, data about the mechanical, physical, and chemical features of bio-fibres were gathered and subjected to a hierarchical analysis prior to the start of the selection process. For this purpose, three physical subcriteria (crystallinity index, density, and moisture content), three mechanical subcriteria (young's modulus, tensile strength, and elongation at break), and three different chemical subcriteria (lignin, hemi-cellulose, and cellulose) were taken into consideration. Subsequently, hierarchy strategies were applied to identify the weights assigned to the attributes based on the notional significance of each attribute.
Keywords: Natural fibre; MCDM; Biomass; Airplane cabin